PP-ZKP: Blockchain-based e-voting system using privacy preserving smart contracts and Zero-Knowledge Proofs - Ali, Mohammad Siraj; Savita, Ashish Kumar; Yadav, Avadhesh; Prasad, Nidhi; Srivastava, Shobhit (Journal of Neonatal Surgery, 2025)
This paper proposes a novel blockchain-based e-voting framework that integrates a permissioned blockchain architecture with privacy-preserving smart contracts using zero-knowledge proofs (ZKPs) to ensure voter anonymity without compromising verifiability. Unlike previous systems, our design includes a lightweight consensus mechanism optimized for high-throughput voting scenarios, addressing the scalability bottleneck commonly found in blockchain applications. We introduce a hybrid on-chain/off-chain verification model that minimizes gas costs while maintaining transparency and auditability. Experimental evaluations using simulated national election datasets demonstrate that our framework achieves a 30% reduction in computational overhead and 50% faster finality compared to existing blockchain-based voting protocols. This work advances the state of e-voting by providing a secure, scalable, and cost-effective solution tailored for modern democratic processes.